2008
DOI: 10.1080/09593330802030069
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet (Uv) Disinfection of Grey Water: Particle Size Effects

Abstract: The impact of water quality on the ultraviolet (UV) disinfection of grey water was investigated with reference to urban water reuse. Direct UV disinfection of grey water did not meet the stringent California State Title 22 criteria for unrestricted urban water reuse due to the presence of particulate material ranging from < 1 to > or = 2000 microm in size. Grey water was manipulated by settling to produce fractions of varying particle size distributions and blending was employed post-disinfection to extract pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…The turbidity and total suspended solids were 1.6 NTU and 2.71 mg/L, respectively, in W2 wastewater, compared with 0.2 NTU and 0.56 mg/L, respectively, in W1 wastewater. This suggests that particles might account for the decreased UV inactivation in W2 wastewater, as attached or embedded bacteria have shown increased resistance to UV inactivation (Winward et al, 2008). Cantwell and Hofmann (2008) reported that particles as small as 11 mm, which are naturally …”
Section: Resultsmentioning
confidence: 99%
“…The turbidity and total suspended solids were 1.6 NTU and 2.71 mg/L, respectively, in W2 wastewater, compared with 0.2 NTU and 0.56 mg/L, respectively, in W1 wastewater. This suggests that particles might account for the decreased UV inactivation in W2 wastewater, as attached or embedded bacteria have shown increased resistance to UV inactivation (Winward et al, 2008). Cantwell and Hofmann (2008) reported that particles as small as 11 mm, which are naturally …”
Section: Resultsmentioning
confidence: 99%
“…A notable concern within this study was the lack of bacterial reduction by 256 UV-C at a dose of 220 mJ·cm −2 , which should have yielded at least a 5-log 10 reduction in viable bacteria (as previously shown by Shoults and Ashbolt [7]). This is not surprising, however, as Winward et al showed a significant decrease in UV-C efficacy of bacterial reduction in water with high turbidity and low UV transmittance [20]. The 256 nm absorbance (A 256 nm) readings ranging from 0.164 to 0.360 (see Table S1) and were not normalized, as given in the unadjusted Equation (1); the A 256 readings would likely have been increased by the use of soap in this study, and thus soap wasn't used.…”
Section: Raw Hand-rinsementioning
confidence: 92%
“…While the effects of large/many suspended particles on the efficacy of UV are understood [20], the role of micro-pollutants and personal care products (PCP) on the efficacy of UV irradiation are relatively unknown. Given the high reported concentrations of the sunscreen benzophenone (BP3), commonly referred to as oxybenzone [21], the effects of oxybenzone on the efficacy of UV irradiation for staphylococci was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…The greater amount of particulates in the concentrated samples might have interfered with antibody specificity and adherence, thus affecting IMS and staining performance. [35,36] The turbidity of the initial sample may be correlated with increased variability of the oocyst counts, as evidenced by the standard deviation value of the recovery (∼15%). Nevertheless, a variability value of approximately 80% for oocyst recovery in >20 NTU surface water was reported for commonly used capsule filters.…”
Section: Number Of Avg Turbidity (Ntu)mentioning
confidence: 98%